Penerapan Model Pembelajaran Kooperatif Tipe STAD dengan Pendekatan SETS terhadap Hasil Belajar Siswa di SMP Arosbaya - Nurul Fitria Ningsih (Pusat Pelatihan, Riset, dan Pembelajaran Bahasa, 2021)
This study aims to describe the students' learning achievement, the implementation of cooperative learning of STAD using SETS approach, and the students’ respond after following the teaching and learning process. This is a pre-experimental study, and the researcher chose one class as the subject of the research, that is, class VIII-i consist of 34 students. The design of the study is one shot case design. The study was conducted for three meetings, two meetings for the teaching and learning process, and one meeting for the administration of cognitive and psychomotor test. The findings of the study shows that the implementation of cooperative learning of STAD using SETS approach in the material of household chemicals have been implemented well based on the syntax in the category of very good (89%). The cognitive aspect of the learning achievement of the successful students were 30 students (88,2%), unsuccessful students were 4 (11,8%). The result of normality test shows that it is normally distributed classes with χscore <χtable (9,5 <11,07) with α = 0,05. The result of t-test of one-tailed obtained tscore> ttable (α = 0,05), with tscore of 4,96 and 1,70 for ttable. This result shows that the implementation of cooperative learning of STAD using SETS approach in the material of household chemicals improves the students’ learning achievement. The students’ performance in the psychomotor aspect is the category of excellent (90,8%), and the affective aspect is in the category of good (84,5%). Based on the results of questionnaires known that students respond positively to the teaching and learning process with the criteria of very good (95,3%).